Pengaruh Pengetahuan Perpajakan, Sosialisasi Perpajakan Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Badan (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Padang Dua) - Ingra Sovita (Jurnal Ekonomi dan Bisnis Digital, 2023)
Influence Of Knowledge Of Taxation, Socialization Of Taxation And Ministry Fiskusagainst Compliancethe Agency's Taxpayer.The purpose of from Research it is to know the influence of taxation knowledge, taxation and service socialization fiskus against taxpayer compliance. Research uses the free variable (X) include namely taxation knowledge (X 1), socialization (X 2), taxation and service fiskus (X 3) and a bound variable (Y), namely the level of Taxpayer compliance Agency (Y). Its population is a whole body of Taxpayers registered in the year 2018 at the Tax Services Office Pratama Padang in two.The sampling techniques used in this research is to accidental sampling is a method of taking of the respondents as the sample is done based on a coincidence, i.e., a condition in which the researcher by accident meet with the respondent are suitable as a data source. The number of samples for Taxpayers residing in the Agency's Office of the Ministry of Taxes Pratama Pasture two amounted to as much as 99.13 Taxpayers or rounded into 100 respondents. Method data collection method used was survey with questionnaire technique. This research use questionnaire instrument. Data analysis methods in use T test, F test, and test R2 with the help of SPSS 21. Instrument data collection using likert scale questionnaire each has been tested and meets the terms of validity and reabilitas.The result of the test coefficient determination showed great influence knowledge of taxation, taxation and service socialization fiskus against taxpayer compliance of 0237 or 23.7%. This shows that influence knowledge of taxation, taxation and service socialization fiskus explains its effect on taxpayer compliance of 23.7%, while the rest amounted to 76.3% is explained by other factors that do not the regression model used in this study.